2007
DOI: 10.1029/2006gb002898
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rising atmospheric carbon dioxide on the marine nitrogen fixer Trichodesmium

Abstract: Diazotrophic (N2‐fixing) cyanobacteria provide the biological source of new nitrogen for large parts of the ocean. However, little is known about their sensitivity to global change. Here we show that the single most important nitrogen fixer in today's ocean, Trichodesmium, is strongly affected by changes in CO2 concentrations. Cell division rate doubled with rising CO2 (glacial to projected year 2100 levels) prompting lower carbon, nitrogen and phosphorus cellular contents, and reduced cell dimensions. N2 fixa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
148
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(169 citation statements)
references
References 42 publications
18
148
3
Order By: Relevance
“…The increase in N 2 fixation or PON production under elevated pCO 2 (Barcelos é Ramos et al 2007;Hutchins et al 2007;Kranz et al 2009;Levitan et al 2007) was found to be caused by a prolongation of the N 2 fixation period (Kranz et al 2010a). As these enhanced N 2 fixation rates were not accompanied by larger protein pools of nitrogenase (Levitan et al 2010b), they may have been achieved by post-translational modification and/or higher energy availability for nitrogenase activity.…”
Section: N 2 Fixationmentioning
confidence: 97%
See 2 more Smart Citations
“…The increase in N 2 fixation or PON production under elevated pCO 2 (Barcelos é Ramos et al 2007;Hutchins et al 2007;Kranz et al 2009;Levitan et al 2007) was found to be caused by a prolongation of the N 2 fixation period (Kranz et al 2010a). As these enhanced N 2 fixation rates were not accompanied by larger protein pools of nitrogenase (Levitan et al 2010b), they may have been achieved by post-translational modification and/or higher energy availability for nitrogenase activity.…”
Section: N 2 Fixationmentioning
confidence: 97%
“…In contrast to other marine b-cyanobacteria (e.g., Anabaena, Crocosphaera, Lyngbya, Nodularia, Synechococcus PCC7002), Trichodesmium lacks CO 2 -responsive genes (CcmR/CmpR) as well as genes associated with high-affinity C i acquisition systems (NDH-1 3 , BCT1, SbtA; Price et al 2008). In view of the strong CO 2 dependence in growth and biomass production (Barcelos é Ramos et al 2007;Hutchins et al 2007;Kranz et al 2009Kranz et al , 2010aLevitan et al 2007), one could assume that the CCM of Trichodesmium functions only insufficiently to saturate the carboxylation reaction of RubisCO . Physiological studies have, however, revealed C i affinities high enough to saturate rates of photosynthesis under CO 2 concentrations typical for the present-day ocean (Kranz et al 2009).…”
Section: Inorganic Carbon Acquisitionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has shown that cell division rate doubled and the Redfield ratios (106C/16N/1P) C/P and N/P (not C/N) of the planktonic cyanobacteria Trichodesmium changed markedly, as a response to increasing levels of CO 2 leading to an enhancement of nitrification and potential enhanced CO 2 drawdown (Barcelos e Ramos et al, 2007). It is believed unlikely, but if this proved to be a selective response in phytoplankton, in general it would establish a strong negative feedback to climate, provided the produced POC sank below the mixed layer.…”
Section: Nutrients In Generalmentioning
confidence: 99%
“…In particular, three studies initiated this interest by documenting increased N 2 -fixation rates by Trichodesmium erythraeum in response to elevated P CO 2 (Barcelos e Ramos et al 2007;Hutchins et al 2007; Levitan et al 2007). It is, however, particularly important to answer questions about how multiple environmental factors might change and interact with rising P CO 2 to affect ocean biogeochemical cycles.…”
mentioning
confidence: 99%